IMPLEMENTATION OF BCM METHODS (PLAYING, STORIES, AND SINGING) TO DEVELOPING SOCIAL-EMOTIONAL INTELLIGENCE OF EARLY CHILDHOOD - Sadiana, Meri; Yulidesni, Yulidesni (TRIADIK, 2016)
Abstract: This classroom action research aimed to describe how social-emotional intelligence primarily the ability to self-motivation and social relationships can be developed through BCM (Play, Story, Singing) methods. The subjects were 15 children (6 females and 9 males) B3 PAUD Negeri Pembina 1 Bengkulu City. The study was conducted in two cycles. Each cycle includes six sessions. Data collected through observation, interviews, and documentation. In applying the method of BCM (Play, Story Singing) the teacher recommended to prepare the things that support the implementation of BCM methods as the form of stories, songs, and games that appeal to the children needs. The results showed that the BCM method developed the child's social and emotional intelligence. The results showed in every aspect of observation has increased at each sessions. The results proved that the method of BCM (Play, Story, Singing) can be developed the child's social and emotional intelligence. The results of counting in every aspect of observation has increased at each sessions. T test results showed there is an increased ability to motivate oneself (t = 8.8, p <0.05) and the ability to establish social relationships (t=7.5, p <0.05). These results were discussed